2001
DOI: 10.4049/jimmunol.167.10.5874
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Th1-Type Response and Resistance toLeishmania majorInfection in the Absence of CD40-CD40L Costimulation

Abstract: CD40-CD40L interactions have been shown to be essential for the production of IL-12 and IFN-γ and control of L. major infection. In contrast, C57BL/6 mice deficient in CD28 develop a dominant Th1-type response and heal infection. In this study, we investigate the effects of a deficiency in both CD40L and CD28 molecules on the immune response and the course of L. major infection. We compared infection in mice genetically lacking CD40L (CD40L−/−), CD28 (CD28−/−), or both (CD40L−/−CD28−/−), and in C57BL/6 mice, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
3
26
0
1
Order By: Relevance
“…However, these studies used a high parasite dose and we have shown that the ability to heal may be directly related to the parasite dose used to initiate infection. Thus, we observed that mice inoculated with 1 ϫ 10 6 promastigotes developed progressive disease, whereas mice inoculated with 2 ϫ 10 4 promastigotes resolved their infections (25). We also showed that healing CD40L deficient mice have numbers of IL-12 producing cells similar to those in control mice suggesting that an alternate pathway of IL-12 production may operate in the absence of CD40-CD40L costimulation (26).…”
Section: Treatment With Tr-fc Reverses Healing In Cd40l Deficient Micesupporting
confidence: 51%
See 2 more Smart Citations
“…However, these studies used a high parasite dose and we have shown that the ability to heal may be directly related to the parasite dose used to initiate infection. Thus, we observed that mice inoculated with 1 ϫ 10 6 promastigotes developed progressive disease, whereas mice inoculated with 2 ϫ 10 4 promastigotes resolved their infections (25). We also showed that healing CD40L deficient mice have numbers of IL-12 producing cells similar to those in control mice suggesting that an alternate pathway of IL-12 production may operate in the absence of CD40-CD40L costimulation (26).…”
Section: Treatment With Tr-fc Reverses Healing In Cd40l Deficient Micesupporting
confidence: 51%
“…The basis of this current study is our previous observation that CD40L Ϫ/Ϫ mice can control L. major infection and develop a dominant Th1 response following inoculation of a reduced number of parasites (25). Thus, an alternate pathway other than CD40-CD40L costimulation must be used in these mice to promote IL-12 production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies show that CD40-CD40L interaction is critical for IL-12 and the development of protective anti-Leishmania immunity (7), others show that CD40L-deficient mice are capable of producing IL-12 and mounting a protective Th1 response against L. major infection (8,9). To fully determine the role of CD40 and CD40L in IL-12…”
Section: Resultsmentioning
confidence: 99%
“…Susceptibility to L. major infection has been linked to a deficiency in the engagement between CD40 and CD40L. 8,[38][39][40][41][42][43][44] Furthermore, B7-mediated costimulation is required for the development of the early immune response following infection of either resistant or susceptible mice. 45 Therefore, activation and maturation of APCs with expression of MHC molecules, CD40 and CD80 on the surface of APCs is fundamental to the process of costimulation of T cells for an efficient response to L. major infection.…”
Section: Discussionmentioning
confidence: 99%